Factors Affecting Customer Interest in Using Mudharabah Saving Accounts at Bank Syariah Indonesia - Nurul Azkiya Izzaty; Manik Mutiara Sadewa (Indonesian Journal of Applied Accounting and Finance, 2024)
Mudharabah savings is a deposit product managed based on a profit-sharing principle between the customer and the bank. Mudharabah savings provide benefits to customers in the form of profit-sharing from the bank's revenue generated from managing the funds. This study aims to analyze the influence of service quality, religiosity, profit sharing, and fund management transparency on customer interest in using Mudharabah savings at Bank Syariah Indonesia. The research method used is quantitative with a descriptive approach. The study's respondents consisted of 96 individuals. Data were collected using a questionnaire and analyzed using multiple linear regression with SPSS Statistics 22. The results of the study indicate that partially 1) service quality has a negative effect on customer interest since the t- value (-0.382) < t-table (1.986), 2) religiosity has a positive effect on customer interest since the t-value (3.139) > t-table (1.986), 3) profit sharing has a positive effect on customer interest since the t-value (2.226) > t-table (1.986), 4) fund management transparency has a positive effect on customer interest since the t- value (2.896) > t-table (1.986). Meanwhile, simultaneously, service quality, religiosity, profit sharing, and fund management transparency positively influence customer interest since the F-value (32.146) > F-table (2.47).